Nonintubated surgical biopsy of undetermined interstitial lung disease: a multicentre outcome analysis. (1st December 2018) - Pompeo, Eugenio; Rogliani, Paola; Atinkaya, Cansel; Guerrera, Francesco; Ruffini, Enrico; Iñiguez-Garcia, Marco Antonio; Peer, Michael; Voltolini, Luca; Caviezel, Claudio; Weder, Walter; Opitz, Isabelle; Cavalli, Francesco; et al.
Abstract: OBJECTIVES: Nonintubated surgical biopsy (NISB) of interstitial lung disease (ILD) has shown promise in unicentre reports as a reliable method to achieve pathological diagnosis with low morbidity. The aim of this study was to investigate for the first time early outcomes of NISB of ILD using a multicentre retrospective analysis. METHODS: Seven European and extra-European institutions participated in the study. Overall, 112 procedures were included. The mean age was 60 ± 12 years (65 men and 47 women). Preoperative total lung capacity and diffusion capacity of carbon monoxide were 74 ± 16% predicted and 57 ± 18% predicted, respectively. Forty-five patients had 1 or more associated comorbidities. NISB of ILD were performed under spontaneous ventilation by intercostal block ( n = 84) or epidural anaesthesia ( n = 28) with ( n = 58) or without ( n = 54) sedation and by thoracoscopic surgery ( n = 88) or minithoracotomy ( n = 24). RESULTS: Mean anaesthesia time, operative time and global time spent in the operating room were 31 ± 31 min, 29 ± 15 min and 89 ± 156 min, respectively. Feasibility was scored as excellent, good, satisfactory or unsatisfactory requiring conversion to general anaesthesia with intubation in 92, 12, 2 and 6 instances, respectively. There were no deaths. Morbidity was 7.1% and included prolonged air leaks in 4 patients and pneumonia, atelectasis, anaemia and gastric bleeding in 1 patient each. A precise pathological diagnosis was achieved in 108 patients (96%). The mean hospital stay was 2.5 ± 2.7 days. Comparisons of results achieved in the largest single-centre series (group A, 60 patients operated on) versus those resulting from the sum of the patients operated on in the other centres (group B, 52 patients operated on) showed no differences in feasibility ( P = 0.10) and morbidity ( P = 0.10) whereas hospital stay was shorter in group A (1.3 ± 0.5 days vs 3.9 ± 3.4 days, P < 0.001). CONCLUSIONS: Results of this multicentre study confirm the satisfactory feasibility of NISB of ILD in 82% of patients with no deaths and a low morbidity rate. Intergroup comparisons indicated that the hospital stay was shorter in group A whereas there were no differences in feasibility and morbidity rates.